The Effectiveness of Auditory, Intellectually and Repetition Learning with RME Approach to Students Mathematical Communication Ability - Nisarohmah, Nur Ilmia; Rochmad, Rochmad; Rosyida, Isnaini (Journal of Primary Education, 2021)
Mathematical communication ability is the ability to model mathematical forms, explain and make questions, and develop arguments. Auditory, Intelectually, and Repetition (AIR) learning facilitates to improve students' mathematical abilities. The purpose of this study was to analyse the effectiveness of auditory, intellectually, repetition learning with a Realistic Mathematics Education (RME) approach on students' mathematical communication ability. This research uses mixed methods with sequential explanatory design. The sampling technique is used by means of cluster random sampling. Data obtained by using the test method, interviews, and observations. Quantitative data analysis was carried out using the t test, the mean difference test, and the proportion test. Based on the results of the study, it shows that the mathematical communication ability of students who use AIR learning with the RME approach on average reach the actual completion limit and classical completion. Students who use auditory, intellectually, repetition learning with a realistic mathematics education approach have better mathematical abilities than students who are taught using problem-based learning. The ability to present sketches, use mathematical notation, then complete and conclude correctly are performed by high mathematical communication skills students. For students with moderate mathematical communication skills, they are quite capable of sketching pictures, applying mathematical notation. Then, students who have low mathematical communication skills are quite capable of sketching pictures, writing mathematical notation. So, it can be concluded that the application of AIR learning with RME approach is effective on students' mathematical communication ability than PBL learning.